2016
DOI: 10.2169/internalmedicine.55.5520
|View full text |Cite
|
Sign up to set email alerts
|

Massive Right Atrial Thrombus Formation Followed by an Atrial Flutter with 1:1 Atrioventricular Conduction in a Patient with Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: A 46-year-old man was admitted to our hospital for near syncope and palpitations. An electrocardiogram showed a common type of atrial flutter (AFL) with 1:1 atrioventricular conduction. Transthoracic echocardiography revealed a massive right atrial (RA) thrombus with a huge RA and right ventricle. The patient was diagnosed with arrhythmogenic right ventricular cardiomyopathy. It was difficult to control the heart rate with beta-blockers during AFL, which resulted in the deterioration of right-sided heart failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Most of the thrombi associated with ACM are thrombi in the RV and only a few case reports have shown ACM complicated with RA thrombi. [7][8][9] In the present case, the patient was under warfarin therapy with adequate prothrombin time-international normalized ratio level (2)(3). The mechanism of the anticoagulation-refractory thrombus formation was speculated to be the blood stasis caused by right ventricular systolic dysfunction, observed as a RA spontaneous echo contrast, and underlying persistent AT.…”
Section: Discussionmentioning
confidence: 71%
“…Most of the thrombi associated with ACM are thrombi in the RV and only a few case reports have shown ACM complicated with RA thrombi. [7][8][9] In the present case, the patient was under warfarin therapy with adequate prothrombin time-international normalized ratio level (2)(3). The mechanism of the anticoagulation-refractory thrombus formation was speculated to be the blood stasis caused by right ventricular systolic dysfunction, observed as a RA spontaneous echo contrast, and underlying persistent AT.…”
Section: Discussionmentioning
confidence: 71%
“…1,2 Previous studies have reported that the arrhythmogenic cardiomyopathy site, associated with thrombus, is generally located in the right ventricle, 3 although there are a few reports of right atrium thrombus. 4,5 Here, we report a rare case of right-sided arrhythmogenic cardiomyopathy complicated with right atrial thrombus, which was detected by echocardiography, with electrocardiography showing typical Epsilon waves, and further confirmation by cardiac magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 85%
“…В большинстве случаев тромбоз полости правого желудочка является составляющим процесса развития тромбоэмболии легочной артерии (ТЭЛА), когда фрагменты тромба свободно располагаются в правых отделах сердца [72][73][74][75][76][77][78]. Вместе с тем известны единичные наблюдения изолированного тромбоза у больных с аритмогенной дисплазией правого желудочка и тромбоза правого желудочка, ассоциированного с имплантируемыми устройствами (электроды ЭКС, катетеры) [79][80][81][82][83][84][85]. Подвижные тромбы в полости правого желудочка, визуализируемые с помощью трансторакальной эхокардиографии, ЧПЭхоКГ или мультиспиральной компьютерной томографии, выявляются менее чем у 4% в общей популяции больных с ТЭЛА, достигая 18% среди больных с субмассивной и массивной ТЭЛА [72][73][74].…”
Section: тромбоз правых отделов сердцаunclassified